Caracterização físico-química de alho comum e nobre em função do tempo de armazenamento - Bessa, Antonia Tamires Monteiro (Universidade Federal Rural do Semi-Árido, 2016)
The post-harvest storage can be an important tool for garlic producers, when the objective is to provide good quality product to the consumer market not only at the time of the harvest, but also to obtain better prices on the market. Thus, the aim with this study was to evaluate the physicochemical characterization of common and noble garlic according to storage time. The experimental design was a randomized complete block design with four replications. The treatments were arranged in split plots, and the plots were represented by garlic cultivars: BRS Hozan and Roxo Pérola de Caçador and the subplots were represented by the storage time: 0, 30, 60, 90 and 120 days after the toilet. We evaluated: weight loss, pith index, soluble solids, total, titratable acidity, pH, soluble solids / titratable acidity, pungency, total solids and industrial index. With the storage time there was an increase in weight loss, pith index and titratable acidity, besides reduction in pH, SS /AT ratio and industrial index. The Roxo Pérola de Caçador had greater storage potential than Hozan cultivar
Physiochemical characterization of common and noble garlic according to storage time
Keywords: Allium sativum L; Pós-colheita; Sólidos solúveis; Pungência; Allium sativum L; Postharvest; Soluble solids; Pungency; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA